2015
DOI: 10.1002/eqe.2615
|View full text |Cite
|
Sign up to set email alerts
|

A numerical model for the dynamic analysis of inclined pile groups

Abstract: Summary The paper presents a numerical model for the dynamic analysis of pile groups with inclined piles in horizontally layered soil deposits. Piles are modelled with Euler–Bernoulli beams, while the soil is supposed to be constituted by independent infinite viscoelastic horizontal layers. The pile–soil–pile interaction as well as the hysteretic and geometric damping is taken into account by means of two‐dimensional elastodynamic Green's functions. Piles cap is considered by introducing a rigid constraint; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Mroueh and Shahrour studied numerically the pull‐out capacity of batter piles and Padrón et al the kinematic internal forces using a coupled boundary element–finite element (FE) method. Numerical studies on the dynamic/seismic behavior of batter piles are also reported in previous studies . Results show that batter piles can have a beneficial or a detrimental role (depending on the earthquake and the superstructure) for soil‐structure dynamic interaction problems.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Mroueh and Shahrour studied numerically the pull‐out capacity of batter piles and Padrón et al the kinematic internal forces using a coupled boundary element–finite element (FE) method. Numerical studies on the dynamic/seismic behavior of batter piles are also reported in previous studies . Results show that batter piles can have a beneficial or a detrimental role (depending on the earthquake and the superstructure) for soil‐structure dynamic interaction problems.…”
Section: Introductionmentioning
confidence: 84%
“…Numerical studies on the dynamic/seismic behavior of batter piles are also reported in previous studies. 15,[20][21][22][23][24][25] Results show that batter piles can have a beneficial or a detrimental role (depending on the earthquake and the superstructure) for soil-structure dynamic interaction problems. Zhang et al 12 suggested modified p − y curves that take into account the pile inclination.…”
Section: Introductionmentioning
confidence: 99%
“…Combination of parameters generates a total of 1470 analysis cases. Analyses of the soil foundations systems are performed by means of the numerical model of Dezi et al (2009), 17 previously recalled, and the non-dimensional components of the impedance matrix of the selected case studies are obtained according to Equations (18).…”
Section: Formulas For Estimating Lpm Parametersmentioning
confidence: 99%
“…By grouping the horizontal components of the soil reaction resultants in sub-vector rh, and denoting by rz the vertical component, vector of the line reaction forces is ( Figure 1b ; u u r (7) where is the 3x3 impedance matrix of the unbounded soil layers. Matrix can be populated considering results of studies by Dobry et al [9], Makris and Gazetas [10] and Gazetas and Dobry [11].…”
Section: Viscoelastic Linear Problemmentioning
confidence: 99%
“…On the contrary, applications of such approaches to inclined piles are not so popular in the literature and more sophisticated finite element or boundary element models are preferred [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%